Multi-physics numerical analyses for predicting the alterations in permeability and reactive transport behavior within single rock fractures depending on temperature, stress, and fluid pH conditions - Sho Ogata; Eita Nishira; Hideaki Yasuhara; Naoki Kinoshita; Toru Inui; Kiyoshi Kishida (Soils and Foundations, 2022)
The aim of the current study was to establish a validated numerical model for addressing the changes in permeability and reactive transport behavior within rock fractures based on the fluid pH under coupled thermal-hydraulic-mechanical-chemical (THMC) conditions. Firstly, a multi-physics reactive transport model was proposed, considering the geochemical reactions that depend on the temperature, stress, and fluid chemistry conditions (e.g., fluid pH and solute concentrations), as well as the changes in permeability in the rock fractures driven by these reactions, after which the correctness of the model implementation was verified by solving the 1D reactive transport problem as a fundamental benchmark. Secondly, the validity of the model against actual rock fractures was investigated by utilizing the model to replicate the measurements of the evolving permeability and the effluent element concentrations in single granite fractures obtained by means of two flow-through experiments using deionized water (pH ∼ 6) and a NaOH aqueous solution (pH ∼ 11) as permeants under stressed, temperature-elevated conditions. The model predictions efficiently followed the changes in fracture permeability over time measured by both experiments. Additionally, the observed difference in the changing rates, which may contribute to the difference in the fluid pH between the two experiments, was also captured exactly by the predictions. Moreover, in terms of the effluent element concentrations, among all the elements targeted for measurement, the concentrations of most elements were replicated by the model within one order of discrepancy. Overall, it can be concluded that the developed model should be valid for estimating the changes in permeability and reactive transport behavior within rock fractures induced by geochemical reactions which depend on the fluid pH under coupled THMC conditions.